Enhancing the Properties of Aluminum AA-1100: The Effect of Mg and Copper Additives with Heat Treatment - BIMA, Bima Wahyu Saputra; Junipitoyo, Bambang (Nusantara Publisher, 2025)
Aluminum alloys, renowned for their low density, high strength, and corrosion resistance, are widely utilized in industries such as aerospace. However, Aluminum 1100 is typically too soft, which necessitates the addition of alloying elements like magnesium (Mg) and copper (Cu) to improve its mechanical properties. This study examines the effects of adding 1.2% magnesium and varying copper concentrations (3.9%, 4.1%, and 4.3%) to Aluminum 1100, followed by heat treatment at 100°C, 200°C, 300°C, and 400°C for 120 minutes. The physical properties, including density, as well as mechanical properties—tensile strength and Vickers hardness—were evaluated. The results revealed that the highest density (3.408 g/cm³) occurred at 300°C with 1.2% Mg and 4.1% Cu. The maximum tensile strength (130.7948 MPa) was observed in the alloy with 4.3% Cu at 400°C, while the highest strain (0.03995%) was recorded at 300°C with 4.3% Cu. The lowest modulus of elasticity (2635.292 MPa) was measured at 100°C with 4.3% Cu, and the highest value (4162.763 MPa) was obtained at 200°C with 4.1% Cu. Additionally, the highest Vickers hardness (90.27 HVN) was achieved in the alloy containing 1.2% Mg and 4.3% Cu at 400°C.